Influence of Regioisomerism in 9‐Anthracenyl‐Substituted Dithiodicyanoethene Derivatives on Photoinduced Electron Transfer Controlled By Intramolecular Charge Transfer. Issue 10 (26th June 2021) - Schwarze, Thomas; Kelling, Alexandra; Sperlich, Eric; Holdt, Hans‐Jürgen
Abstract: In this paper, we report on the fluorescence behaviour of three regioisomers which consist of two 9‐anthracenyl fluorophores and of differently substituted dithiodicyanoethene moieties. These isomeric fluorescent probes show different quantum yields ( ϕ f ). In these probes, an oxidative photoinduced electron transfer (PET) from the excited 9‐anthracenyl fluorophore to the dithiodicyanoethene unit quenches the fluorescence. This quenching process is accelerated by an intramolecular charge transfer (ICT) of the push‐pull π‐electron system of the dithiodicyanoethene group. The acceleration of the PET depends on the strength of the ICT unit. The higher the dipole moment of the ICT unit, the stronger the observed fluorescence quenching. To the best of our knowledge, this is the first report of a regioisomeric influence on an oxidative PET by an ICT. Abstract : A photoinduced electron transfer (PET) process is controlled by the strength of an intramolecular charge transfer (ICT) in isomeric 9‐anthracenyl‐substituted dithiodicyanoethene derivatives. The strength of the ICT unit regulates the effectiveness of the fluorescence quenching within these fluorescent probes.